Choosing a technique for severe hypospadias - Alexis Arnaud; Luke Harper; Marie-Benedicte Aulagne; Jean-Luc Michel; Aude Maurel; Eric Dobremez; Laurent Fourcade; Lalatiana Andriamananarivo (Wolters Kluwer Medknow Publications, 2011)
Introduction: We participate in humanitarian missions in Madagascar during which we treat severe hypospadias. We report our experience and results with these patients, in these conditions, and discuss our choice of technique in this particular setting. Materials and Methods: We retrospectively reviewed the data of 27 patients operated for severe hypospadias during our humanitarian missions in Madagascar between November 2006 and September 2009. Twenty one patients underwent a modified Koyanagi procedure, three underwent a Duckett urethroplasty, two an onlay island flap, one an augmented Duckett and one a tubularised plate urethroplasty. Two patients who underwent a modified Koyanagi repair also had a Nesbitt dorsal plication. Results: Patient age at the time of surgery ranged from 22 to 198 months with a median age of 54.1 months. Mean follow-up was 16 months. Of the 21 patients who underwent a modified Koyanagi procedure, 16 presented at least one complication (76%): A fistula developed in 12 patients (57%), meatal regression developed in 7 (33%) and 2 showed complete wound dehiscence (9.5%). None developed stenosis or urethrocoele. Conclusion: In this particular setting, the postoperative complication rate is high. Nevertheless, the Koyanagi technique is appropriate, because its complications are easy to treat and there is always sufficient ventral tissue for the secondary operation, if necessary.